2020
DOI: 10.1021/acs.jpcc.0c03576
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Sensitive Vibrational SFG Spectra from Simple Classical Force Field Molecular Dynamics Simulations

Abstract: We show that phase-sensitive vibrational sum frequency generation (SFG) spectra of solid/water and air/water interfaces, neutral and charged, can be successfully predicted using classical molecular dynamics (CMD) simulations in combination with simple nonpolarizable force fields (FFs). This can be achieved when employing velocity−velocity autocorrelation functions weighted by parameterized Raman and atomic polar tensors for the computation of the SFG. This procedure avoids computing polarizability tensors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…152,153,165 The new Clayff parametrization of the Al−O−H bending terms 152 has been recently successfully used to accurately reproduce the complex phase-sensitive vibrational sum frequency generation spectra of water on a fully hydroxylated (0001) surface of alumina. 166 Zhang and co-workers 108 have recently used the extended potentials (Pouvreau et al, 2017) of Clayff to model the interaction of soil organic matter with basal and edge surfaces of clay nanoparticles (Figure 5f and i).…”
Section: Advances In Clayffmentioning
confidence: 99%
See 1 more Smart Citation
“…152,153,165 The new Clayff parametrization of the Al−O−H bending terms 152 has been recently successfully used to accurately reproduce the complex phase-sensitive vibrational sum frequency generation spectra of water on a fully hydroxylated (0001) surface of alumina. 166 Zhang and co-workers 108 have recently used the extended potentials (Pouvreau et al, 2017) of Clayff to model the interaction of soil organic matter with basal and edge surfaces of clay nanoparticles (Figure 5f and i).…”
Section: Advances In Clayffmentioning
confidence: 99%
“…Importantly, such an angle term can be implemented while still maintaining the nonbonded pair interactions of Clayff. Parameters have been derived for cations in octahedral (Mg–O–H and Al–O–H) and tetrahedral (Si–O–H) coordination. ,, The new Clayff parametrization of the Al–O–H bending terms has been recently successfully used to accurately reproduce the complex phase-sensitive vibrational sum frequency generation spectra of water on a fully hydroxylated (0001) surface of alumina . Zhang and co-workers have recently used the extended potentials (Pouvreau et al, 2017) of Clayff to model the interaction of soil organic matter with basal and edge surfaces of clay nanoparticles (Figure f and i).…”
Section: Advances In Clayffmentioning
confidence: 99%
“…However, the high expenditures of such calculations strongly limit the size of studied systems, sampling time and the accessible range of electrolyte concentrations. On the other hand, MD simulations using effective potentials permit to obtain nonlinear spectra of significantly bigger systems for much longer trajectories and thus, with an improved statistical sampling 43,[50][51][52][53][54] . Thus, a recent classical MD study of several neutral silica/water interfaces has shown that the Im[χ (2) ] spectrum of BIL features both the negative 3200 cm −1 and positive 3400 cm −1 bands with a surface-specific shape of the latter 54 .…”
Section: Introductionmentioning
confidence: 99%
“…With this respect, classical MD simulations of mineral/water interfaces permit to investigate much larger systems for longer period of time, and yield phase-sensitive VSFG spectra in a good agreement with both experiments and ab initio MD. 38,42 Characteristics of neutral silica/water interfaces are important reference data and their analysis allows to get a revealing insight into the behavior of the more realistic systems. The purpose of the present work is to study the relationship between the structure of water on neutral hydroxylated silica surfaces and the VSFG spectrum of the interface as a function of the surface and liquid phase composition.…”
Section: Introductionmentioning
confidence: 99%